Трансшипмент как перспективное направление развития контейнерных перевозок - Опанчук, Б.А. (Економічні інновації, 2010)
У статті розглядається конкурентне положення українських контейнерних терміналів на ринку трансшипмента та фідерних перевезень в Чорноморському регіоні. Запропоновано ряд організаційних заходів щодо сприяння розвитку цього виду перевезень в Україні, який, в свою чергу, сприяє реалізації транзитного потенціалу держави. In the article the competitive position of Ukrainian container terminals on the Black Sea container shipping market is considered. There are many difficulties appearing by handling of containers moving through Ukrainian ports. Taking into consideration the intensive development of neighboring Black sea container terminals, the possibility that Ukraine could get beyond the European transport network, the necessity of taking critical decisions for transit status of Ukrainian ports, is also acute today.